Supporting Student's Ability in Understanding Least Common Multiple (LCM) Concept Using Storytelling - Triyani, Septi; Darmawijoyo, Darmawijoyo; Putri, Ratu Ilma Indra (Journal on Mathematics Education, 2012)
Several researches showed that students had difficulty in understanding the concept of Least Common Multiple (LCM) in Elementary School. This underlies the researcher to design a learning of LCM  using storytelling,  Legend Putri Dayang Merindu  (LPDM), which contains situational problem related to LCM. The purposes of this study are  to know  the role  of  LPDM in supporting students'  ability to understand LCM concept and  to generate a student  learning  trajectory in  learning of LCM  using LPDM.  This research  uses methodology of design research consists of three steps (i.e.  preliminary design, teaching experiment  andÂ  retrospective analysis),  and the learning approach of realistic mathematics education, labeled by  PMRI  in Indonesia. From the research result conducted in MIN 1 Palembang can be concluded that the learning of LCM using LPDM has role in supporting students' ability to understand LCM concept. Therefore, student learning trajectory to understanding LCM concept is started from solving of situational problems based on LPDM until formal solution of LCM. In this case, there are three stages that students through (i.e. understanding concept of multiple, common multiple and LCM) using various strategies in the level situational, model of, model for and formal.